Study on dynamic alterations of plasma lipid profiles during disease progression in combined allergic rhinitis and asthma syndrome based on lipidomics - Shi, Yanmin; Li, Yiting; Cheng, Zifan; Wang, JiaJia; Li, Suyun; Xie, Yang (Frontiers in Immunology, 2025)
Combined allergic rhinitis and asthma syndrome (CARAS) involves complex interactions between inflammation and lipid metabolism. This study recruited 90 CARAS patients admitted to the First Affiliated Hospital of Henan University of Chinese Medicine from August 2023 to August 2024 (30 cases each for CARASa, CARASb and CARASc), along with 30 healthy controls (HC). We systematically profiled serum lipidomes across different CARAS stages and examined associations with inflammatory cytokines and mucins. Baseline characteristics were comparable among healthy controls (HC) and CARAS subgroups. CARAS patients in the acute phase (CARASa) exhibited elevated serum-specific IgE and fractional exhaled nitric oxide, indicating heightened allergic sensitization, while pulmonary function remained preserved. Lipidomic analysis revealed a pronounced shift from fatty acids to glycerolipids in CARASa, with upregulation of triglycerides, digalactosyldiacylglycerol, phosphatidylserines, phosphatidylethanolamines, and ceramides. CARASb (chronic persistence) showed persistent dysregulation of sphingomyelins, lysophosphatidylcholines, and membrane lipids, whereas CARASc (clinical remission) exhibited partial recovery with residual alterations in specific lipid classes. Correlation analysis indicated that fatty acid depletion strongly associated with glycerolipid accumulation. Pathway enrichment highlighted stage-dependent disturbances in fatty acid transport, GLP-1/incretin turnover, sphingolipid biosynthesis, and retinoid metabolism, reflecting metabolic-immune crosstalk. Notably, differential lipids (Digalactosyldiacylglycerol, phosphatidylethanolamines and phosphatidylserine) positively correlated with pro-inflammatory cytokines (TNF-α, IL-6) and mucins (MUC1, MUC5AC) in CARASa and CARASb groups. In the CARASc group, these differential lipids showed a negative correlation with pro-inflammatory factors and mucins. These findings define a trajectory of stage-specific lipid metabolic remodeling in CARAS, linking energy metabolism and membrane lipid changes to inflammatory activation and mucin expression, providing potential metabolic biomarkers and therapeutic targets.